The Effect Of Guided Inquiry Model Assisted By Lkpd To Improve Students' Creative Thinking Abilities On Momentum And Impulse Materials At Sman 1 Pagai Utara - Tasirieleu, Nisika (Department of Physics Universitas Negeri Padang, 2025)
This research aims to show that students' creative thinking abilities can be improved in physics learning through a guided inquiry model so that students' creative thinking abilities can reach a high category in physics learning. This research is a pre-experiment with a one group pretest-posttest design. The population of this study were phase F students of SMAN 1 Pagai Utara. The sample in this research was taken using a simple random sampling technique. The research instruments used were essay test questions, observation sheets, and performance assessments. Based on the description that has been presented, the researcher wants to conduct research on the influence of the guided inquiry model assisted by LKPD to improve creative thinking skills.